A prospective phase II randomized trial of proton radiotherapy vs intensity-modulated radiotherapy for patients with newly diagnosed glioblastoma. Issue 8 (27th February 2021) - Brown, Paul D; Chung, Caroline; Liu, Diane D; McAvoy, Sarah; Grosshans, David; Al Feghali, Karine; Mahajan, Anita; Li, Jing; McGovern, Susan L; McAleer, Mary-Fran; Ghia, Amol J; Sulman, Erik P; et al.
Abstract: Background: To determine if proton radiotherapy (PT), compared to intensity-modulated radiotherapy (IMRT), delayed time to cognitive failure in patients with newly diagnosed glioblastoma (GBM). Methods: Eligible patients were randomized unblinded to PT vs IMRT. The primary endpoint was time to cognitive failure. Secondary endpoints included overall survival (OS), intracranial progression-free survival (PFS), toxicity, and patient-reported outcomes (PROs). Results: A total of 90 patients were enrolled and 67 were evaluable with median follow-up of 48.7 months (range 7.1-66.7). There was no significant difference in time to cognitive failure between treatment arms (HR, 0.88; 95% CI, 0.45-1.75; P = .74). PT was associated with a lower rate of fatigue (24% vs 58%, P = .05), but otherwise, there were no significant differences in PROs at 6 months. There was no difference in PFS (HR, 0.74; 95% CI, 0.44-1.23; P = .24) or OS (HR, 0.86; 95% CI, 0.49-1.50; P = .60). However, PT significantly reduced the radiation dose for nearly all structures analyzed. The average number of grade 2 or higher toxicities was significantly higher in patients who received IMRT (mean 1.15, range 0-6) compared to PT (mean 0.35, range 0-3; P = .02). Conclusions: In this signal-seeking phase II trial, PT was not associated with a delay in time to cognitive failure but did reduce toxicity and patient-reported fatigue. Larger randomized trials are needed to determine the potential of PT such as dose escalation for GBM and cognitive preservation in patients with lower-grade gliomas with a longer survival time.